2006
DOI: 10.1111/j.1462-5822.2006.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent role of the phosphatidylinositol-3-kinase (PI3K) during influenza virus infection and host cell defence

Abstract: SummaryInfections with influenza A viruses result in the activation of a variety of intracellular signalling pathways. Recent findings suggest that in response to doublestranded RNA (dsRNA), which is commonly used as a mimic for accumulating viral RNA, the phosphatidylinositol-3-kinase (PI3K) is activated and mediates activation of the transcription factor interferon regulatory factor 3 (IRF-3). Thus, we investigated the function of PI3K during influenza virus infection. The pathway was activated upon infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
263
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(290 citation statements)
references
References 46 publications
25
263
1
1
Order By: Relevance
“…In addition, it is known that the NS1 protein produced by IAV binds to the p85β subunit of PI3K to induce PI3K activity in infected cells (44). Finally, pharmacological intervention with inhibitors of PI3K and rapamycin block IAV replication in vitro, which is consistent with a role for the PI3K/ Akt/mTOR pathway in IAV infection (33,45).…”
Section: Discussionsupporting
confidence: 56%
“…In addition, it is known that the NS1 protein produced by IAV binds to the p85β subunit of PI3K to induce PI3K activity in infected cells (44). Finally, pharmacological intervention with inhibitors of PI3K and rapamycin block IAV replication in vitro, which is consistent with a role for the PI3K/ Akt/mTOR pathway in IAV infection (33,45).…”
Section: Discussionsupporting
confidence: 56%
“…The intensity of the bands was quantitated by an image analyser, and the fold increase in GTP-bound/total Ras is shown at the bottom. former two correspond to the periods before and after replication initiation, respectively 7,22 ( Supplementary Fig. S3d).…”
Section: Resultsmentioning
confidence: 99%
“…We and others have previously shown that PI3K is required for CIE and influenza virus infection 7,22 , and Epsin1 has been found to be required for virus internalization via CME 5 . However, the molecular mechanisms by which influenza viruses exploit CIE and CME for their efficient internalization by host cells have remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, a number of studies have shown that influenza virus can effectively activate the MAPK pathways and the activation of MAPK family members plays an important role in viral replication, proinflammatory and apoptotic response in various cells during influenza virus infection [6974]. Moreover, the PI3K/Akt/mTOR pathway also activated during influenza virus infection and function as supporting viral effective replication [7580]. …”
Section: Discussionmentioning
confidence: 99%